Flocculation in industrial strains of Saccharomyces cerevisiae: role of cell wall polysaccharides and lectin‐like receptors. Issue 2 (29th March 2017) - Nayyar, Ashima; Walker, Graeme; Wardrop, Forbes; Adya, Ashok K.
Abstract : Yeast flocculation is the reversible aggregation of yeast cells promoted by the interaction between lectin‐like protein receptors with mannose side chains on adjacent cell walls. Flocculation is governed by several physiological factors, including the type of nutrient sugar available to yeast. We grew four industrial strains of Saccharomyces cerevisiae, representing applications in the brewing, winemaking and bioethanol sectors, to late stationary phase and quantified the cellular content of mannans, glucans and lectin‐like proteins on yeast cell surfaces. Results indicated that brewing and champagne strains showed moderate to high flocculation ability when grown with glucose, fructose, maltose or galactose, whereas winemaking and fuel alcohol strains only showed moderate flocculation when grown on maltose and galactose. All yeast strains studied were weakly flocculent when grown on mannose. With regard to lectin‐like receptors, their number played a more important role in governing yeast flocculation than the mannan and glucan contents in yeast cell walls. We conclude that all the industrial strains of S. cerevisiae belonged to New‐Flo type on the basis of their flocculation behaviour observed when cultured on different sugars. Quantification of yeast cell wall polysaccharides and receptor sites indicates that mannan and glucan levels remain almost constant, irrespective of the strain under investigation. The main difference in flocculation characteristics in industrial yeast strains appears to be due to variations in concentrations of lectin‐like cell surface receptors. Our findings may benefit brewers, winemakers and other yeast‐based technologies in design of media to prevent premature flocculation during fermentation. Copyright © 2017 The Institute of Brewing & Distilling